Comparative study of ultrasonographic methods for assessment of pregnancy age in bitches - Castro, Viviane Montich de [UNESP]; Mamprim, Maria Jaqueline [UNESP]; Lopes, Maria Denise [UNESP]; Sartor, Raquel [UNESP] (Univ Federal Rural Pernambuco, 2011)
Compared with human beings, the application of ultrasound in estimating fetal age in bitches is limited due to the large variation of breed and size in this species. Several formulas were developed to calculate the gestational age and to provide the date of birth in dogs, but the efficacy of these formulas on the different gestational stages and dog breeds is unknown. The aim of this study was to compare sonographic methods for assessment of gestational age and days before parturition in dogs with different body weights and pregnancy stages. Twenty seven bitches of several sizes were examined and divided into three groups according to the initial body weight (A: <10kg; B: 10.1 - 20kg; C: >20.1kg); then each group was divided into three subgroups according to pregnancy stage (1st: 18 to 30 days; 2nd: 31 to 40 days; 3rd: >40 days) estimated according to the first day of copulation. Ultrasonography was performed weekly from the first stage of pregnancy. In the first and second stage the following formulas were applied: GA = (6XGSD) + 20; DBP = 65 - IG; by Nyland & Matton (2002); GA: gestational age; DBP: days before parturition; DSG: gestational sac diameter; in the third stage: DBP = 61,2 - (24,6 X BD); DBP = 43,5 - (10,9 X CD); by Burk & Ackerman (1996); BD: biparietal diameter; CD: body diameter, and: GA = (15 X BD) + 20; GA = (7 X CD) + 29; GA = (6 X BD) + (3 X CD) + 30; DBP = 65 - GA; by Nyland & Matton (2002). Results were compared statistically. The equations proposed by Nyland & Matton (2002), were more accurate in all pregnancy stages, with a margin of error of only three days, regardless of the size of the animal; therefore these methods are the best option in veterinary practice.
Keywords: Ultrasound; bitches; pregnancy; diagnosis; gestational age